Overview of Reformatting Equipment - University of Wisconsin Digital Collections Center (My University, 2006)
Gives a list of the UWDCC's reformatting equipment, as well as what the equipment is used for.
Keywords: Reformatting Equipment; University of Wisconsin Digital Collections Center